The Protection of Right to Life and Abortion - Simeunović-Patić, Biljana; Jovanović, Slađana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2007)
The paper analyses the issue of the right to choose abortion within the context of conflict of fetuses’ and mothers’ interests, i.e. conflict between the fetus's right to life and the mother’s right to privacy and procreative rights. It has been given a summary on the permissibility of abortion in historical perspective, as well as an overview of contemporary models of abortion regulation. It has been referred to factos that factors contribute to the permissibility of abortion as a complex problem which includes various legal, moral, medical, cultural and social dimensions. The conclusions include that termination of unwanted pregnancy, as well as unwanted parenthood, constitute composite social problems whose solving has to be seriously and comprehensively approached, employing the measures that should not and must not be reduced to limitation of women’s right to access abortion.